Peran Museum Tani Jawa Indonesia dalam Peningkatan Kinerja Desa Wisata Candran Bantul - Hardi Wahyuno (Media Wisata, 2015)
Since the tourist arrives at the location as a rural marketplace, they will get soon their gaze, as they watch some products. These products include location, price, service, facilities, images, in the dynamic of the development of the local people. The local people are considered to be suppliers of the product, as seen in the tourism point of view. The basic point of view of the tourist is the romanticism and nostalgia is experienced at the location and it’s relation with the tourist capacity and capability to understand some associations of the products, as products are categorized and branded, underneath they are the controlled as well as the tourist understand the meaning of the symbols locally, in the form of cultural goods. This case raises up some tourism consideration which this will be studied in the field of comparative rural tourism, heritage tourism. The tourists have their own criteria in understanding people‘s way of life, development, condition, in their locality and in the other hand is the people, the way they understand the tourists’ needs and wants. The relation between local people and tourists attitude is in this contact, communicates the ongoing matter of tourism. The attitude of the local people in the tourist village in Chandran, they are the creator of their heritage. The heritage has a role for them, because its value, in several degrees, is correlatively connected with local history, culture, and nature. This is important to understand local heritage tourism. Diversity of the dynamic rtelation between the village and the city in the tourisme context is significant and it’s difference is understood. The village, it’s self, in the tourisme context, stengthens the destination of Jogjakarta by producing the tourist village in the setting of rural tourisme, heritage tourisme. Tourist needs and wants of the rural as product (tangible-intangible) to consume , the local people make some supplies as attraction, acces includes catergorical and brand, where the product : tourist village is typical and specific, valueable, increases the power of attraction , because of it’s content, where people respons to challenge in their locality at location. The location (historicval, cultural, natural aspect) can increase tourist’s motivation, inisiate the pulled factor, and forme the heritage tourisme, rural tourisme.The role of the people, in their every day life, is as induvidual or collective local actor, they do, they create heritage for them, they expresse visually, in their attitude toward tourist (performence), as well as their attitude is focused at the rural museum. The people acts as cultural model, authentic, fixing up the proses of consumption (economics). The product to consume is attached with it’s association and it’s symbolic meaning (cultural). The Museum Tani Jawa Indonesia in Candran increase the selling value of it’s locality and try to fit with the standard expectation toward the global standar as this is the matter of the field in the comparative rural, heritage tourisme.